Potency of descending pain modulatory system is linked with peripheral sensory dysfunction in fibromyalgia: An exploratory study. Issue 3 (January 2019) - Brietzke, Aline Patrícia; Antunes, Luciana Conceição; Carvalho, Fabiana; Elkifury, Jessica; Gasparin, Assunta; Sanches, Paulo Roberto Stefani; da Silva Junior, Danton Pereira; Dussán-Sarria, Jairo Alberto; Souza, Andressa; da Silva Torres, Iraci Lucena; Fregni, Felipe; MD, Wolnei Caumo
Abstract : Abstract: Fibromyalgia (FM) is characterized by chronic widespread pain whose pathophysiological mechanism is related to central and peripheral nervous system dysfunction. Neuropathy of small nerve fibers has been implicated due to related pain descriptors, psychophysical pain, and neurophysiological testing, as well as skin biopsy studies. Nevertheless, this alteration alone has not been previously associated to the dysfunction in the descending pain modulatory system (DPMS) that is observed in FM. We hypothesize that they associated, thus, we conducted a cross-sectional exploratory study. To explore small fiber dysfunction using quantitative sensory testing (QST) is associated with the DPMS and other surrogates of nociceptive pathways alterations in FM. We run a cross-sectional study and recruited 41 women with FM, and 28 healthy female volunteers. We used the QST to measure the thermal heat threshold (HTT), heat pain threshold (HPT), heat pain tolerance (HPT), heat pain tolerance (HPTo), and conditional pain modulation task (CPM-task). Algometry was used to determine the pain pressure threshold (PPT). Scales to assess catastrophizing, anxiety, depression, and sleep disturbances were also applied. Serum brain-derived neurotrophic factor (BDNF) was measured as a marker of neuroplasticity. We run multivariate linear regression models by group to study their relationships. Samples differed in their psychophysical profile, where FM presented lower sensitivity and pain thresholds. In FM but not in the healthy subjects, regression models revealed that serum BDNF was related to HTT and CPM-Task (Hotelling Trace = 1.80, P  < .001, power = 0.94, R 2  = 0.64). HTT was directly related to CPM-Task ( B  = 0.98, P  = .004, partial- η 2  = 0.25), and to HPT ( B  = 1.61, P  = .008, partial η 2  = 0.21), but not to PPT. Meanwhile, BDNF relationship to CPM-Task was inverse ( B  = –0.04, P  = .043, partial- η 2  = 0.12), and to HPT was direct ( B  = –0.08, P  = .03, partial- η 2  = 0.14). These findings high spot that in FM the disinhibition of the DPMS is positively correlated with the dysfunction in peripheral sensory neurons assessed by QST and conversely with serum BDNF.